2018
DOI: 10.3982/ecta14370
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ambiguity Attitudes for All (Natural) Events

Abstract: Measurements of ambiguity attitudes have so far focused on artificial events, where (subjective) beliefs can be derived from symmetry of events and can be then controlled for. For natural events as relevant in applications, such a symmetry and corresponding control are usually absent, precluding traditional measurement methods. This paper introduces two indexes of ambiguity attitudes, one for aversion and the other for insensitivity/perception, for which we can control for likelihood beliefs even if these are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 117 publications
3
70
0
Order By: Relevance
“…One solution for applied empirical researchers may then be to recur to more natural sources of uncertainty (Abdellaoui et al, 2011;Baillon, Huang, Selim and Wakker, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution for applied empirical researchers may then be to recur to more natural sources of uncertainty (Abdellaoui et al, 2011;Baillon, Huang, Selim and Wakker, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…This will mean focusing on natural sources of uncertainty, as some studies have already done (Abdellaoui et al, 2011;Baillon, Bleichrodt, Keskin, l'Haridon and Li, 2016a). Baillon et al (2016b) proposed a method for the nonparametric measurement of ambiguity attitudes and showed that it exhibits high levels of measurement reliability. This may also mean moving away from a comparison point of risk, which can hardly ever be found in reality, and towards varying degrees of ambiguity underlying outcome-generating processes.…”
mentioning
confidence: 99%
“…In this paper, we measure ambiguity attitudes toward return distributions that investors typically face when making portfolio choices. We employ a new method devised by Baillon, Huang, Selim, and Wakker (2018b) to elicit ambiguity attitudes for these natural sources of ambiguity instead of artificial events, while controlling for unknown probability beliefs. This method overcomes the well-known problem that, when observing a dislike of ambiguous options, this could be due either to ambiguity aversion or to pessimistic beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Butler et al (2014) found using a representative survey and large-scale behavioral experiments that individuals reporting being prone to use more intuitive (rather than also deliberative) reasoning style are less often averse to ambiguity (and also to well-defined risk), but see Bergheim and Roos (2013). Recently, Baillon et al (2018) elicited winning probabilities that were considered as good as winning contingent on natural events (stock exchange index change being within a specified range), with and without time pressure. They found that time pressure does not affect ambiguity aversion but appears to increase ambiguity generated-insensitivity, a tendency analogous to inverse-S probability weighting.…”
Section: Introduction and Brief Review Of Related Experimentsmentioning
confidence: 99%